Planning instruction [videorecording] - Morgan, Nancy Battista; Alvarez, Ana; KNB Productions; Magna Systems (Chicago, I.L. : Magna Systems)
Explains how to plan meaningful instruction by understanding students' developmental stages, developing a deeper understanding of content, and crafting valid objectives and assessments to inform instruction. Describes successful lesson planning as a combination of scheduling, conceptual organization, and practical implementation. Shows how to use assessments to design instructions, how to weave together many different sources in planning instruction, and how to activate prior knowledge. Features veteran teachers who provide a glimpse into their lesson-planning processes, sharing tricks and tips they've learned along the way